Are the current notification criteria for Lyme borreliosis in Norway suitable? Results of an evaluation of Lyme borreliosis surveillance in Norway, 1995–2013. (December 2016) - MacDonald, Emily; Vestrheim, Didrik; White, Richard; Konsmo, Kirstin; Lange, Heidi; Aase, Audun; Nygård, Karin; Stefanoff, Pawel; Aaberge, Ingeborg; Vold, Line
Abstract Background The approach to surveillance of Lyme borreliosis varies between countries, depending on the purpose of the surveillance system and the notification criteria used, which prevents direct comparison of national data. In Norway, Lyme borreliosis is notifiable to the Surveillance System for Communicable Diseases (MSIS). The current notification criteria include a combination of clinical and laboratory results for borrelia infection (excluding Erythema migrans) but there are indications that these criteria are not followed consistently by clinicians and by laboratories. Therefore, an evaluation of Lyme borreliosis surveillance in Norway was conducted to describe the purpose of the system and to assess the suitability of the current notification criteria in order to identify areas for improvement. Methods The CDC Guidelines for Evaluation of Surveillance Systems were used to develop the assessment of the data quality, representativeness and acceptability of MSIS for surveillance of Lyme borreliosis. Data quality was assessed through a review of data from 1996 to 2013 in MSIS and a linkage of MSIS data from 2008 to 2012 with data from the Norwegian Patient Registry (NPR). Representativeness and acceptability were assessed through a survey sent to 23 diagnostic laboratories. Results Completeness of key variables for cases reported to MSIS was high, except for geographical location of exposureThe NPR-MSIS linkage identified 1047 cases in both registries, while 363 were only reported to MSIS and 3914 were only recorded in NPR. A higher proportion of cases found in both registries were recorded as neuroborreliosis in MSIS (84.4 %) than those cases found only in MSIS (20.1 %). The trend (average yearly increase or decrease in reported cases) of neuroborreliosis in MSIS was not significantly different from the trend for all other clinical manifestations recorded in MSIS in negative binomial regression (p = 0.3). The 16 surveyed laboratories (response proportion 70 %) indicated differences in testing practices and low acceptability of the notification criteria. Conclusions Given the challenges associated with diagnosing Lyme borreliosis, the selected notification criteria should be closely linked with the purpose of the surveillance system. Restricting reportable Lyme borreliosis to neuroborreliosis may increase validity, while a more sensitive case definition (potentially including erythema migrans) may better reflect the true burden of disease. We recommend revising the current notification criteria in Norway to ensure that they are unambiguous for clinicians and laboratories.